PENGARUH PENDEKATAN PROBLEM SOLVING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS IX SMPN 7 MERANGIN - Nurmaliati; Nora Hardista (Mat-Edukasia, 2016)
This study was motivated by the low mathematical communication of grade IX students at Merangin 7 Public High School. This is due to the lack of active students in the learning process, students only listen to what the teacher explains without understanding it, so students have not been able to communicate mathematically. To overcome this, the researcher uses a problem solving approach. This study aims to determine whether the mathematical communication skills of class IX students of SMP N 7 Merangin in the 2015/2016 Academic Year taught by problem solving approaches are better than those taught by conventional learning. This type of research is quantitative research with experimental methods. The sample in this study was IXB as the experimental class and IXC class as the control class. Data collected using the technique of mathematical communication skills in the form of essay on congruence material. The data analysis technique used to test the hypothesis is the t-test, because the data are normally distributed and have a homogeneous variance. From the data analysis, the experimental class obtained an average of 73,098, whereas in the control class the average is 59,524. . Hypothesis test results obtained, = 3.802 and = 1.864. Because> then Ho is rejected and Ha is accepted. So it was concluded that there was an effect of problem solving approach on mathematical communication skills of class IX students of SMP N 7 Merangin in the 2015/2016 school year .Keywords: Mathematical communication skills, problem solving approach